ANALISIS RANTAI PASOK (Supply Chain) KEDELAI DI UD ADEM AYEM KECAMATAN PULOKULON KABUPATEN GROBOGAN - Ahmad Dany Fadhlullah (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The purpose of this research is to analyze 1) the product flow, financial flow and soybean information flow at UD Adem Ayem and 2) the marketing margins and marketing efficiency of the supply chain at UD Adem Ayem. The research method used is a case study. Respondent determination method used is purposive sampling method for respondent intermediary traders at UD Adem Ayem and accidental sampling for farmer and consumer respondents. The analysis used is descriptive analysis and quantitative analysis by calculating marketing margins, marketing share and marketing efficiency. Research shows that there are 3 flows in the UD Adem Ayem soybean supply chain namely product flow, financial flow and information flow. UD Adem Ayem's supply chain has one soybean supply chain pattern, namely producers (soybean farmers), UD Adem Ayem (collectors), wholesalers and consumers and has three supply chain networks, namely large traders outside the sub-district, outside the district and outside Central Java province. Network 1's marketing margin is Rp. 710.00, network 2 is Rp. 1,485.00 and network 3 is Rp. 1,410.00. The marketing efficiency of UD Adem Ayem soybeans is efficient with Farmer ‟s network 1 share value of 89.55%, network 2 of 80.39% and network 3 of 81.20%.